1997
DOI: 10.1016/s0969-2126(97)00284-0
|View full text |Cite
|
Sign up to set email alerts
|

The crystal structure of vascular endothelial growth factor (VEGF) refined to 1.93 Å resolution: multiple copy flexibility and receptor binding

Abstract: A comparison of the eight independent copies of VEGF in the asymmetric unit indicates the conformational space sampled by the protein in solution; the root mean square differences observed are similar to those seen in ensembles of the highest precision NMR structures. Mapping the receptor-binding determinants on a multiple sequence alignment of VEGF homologs, suggests the differences in specificity towards KDR and Flt-1 may derive from both sequence variation and changes in the flexibility of binding loops. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
198
0
3

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(212 citation statements)
references
References 69 publications
11
198
0
3
Order By: Relevance
“…The crystal structure of VEGF has recently been reported (33,41 17 and Glu 64 from the second monomer (33). The presence of five hydrophobic residues in the binding site on VEGF implies that part of the binding site on the receptors also contains hydrophobic residues.…”
Section: Discussionmentioning
confidence: 99%
“…The crystal structure of VEGF has recently been reported (33,41 17 and Glu 64 from the second monomer (33). The presence of five hydrophobic residues in the binding site on VEGF implies that part of the binding site on the receptors also contains hydrophobic residues.…”
Section: Discussionmentioning
confidence: 99%
“…1B). Recently, the crystal structure study for PlGF (29) revealed that PlGF actually conserves the tertially structure with VEGF (30,31) and PDGF (32). Thus, the VEGF-E NZ-7 /PlGF chimera mutants were assumed to fold appropriately in a similar manner and build up tertiary structure.…”
Section: Discussionmentioning
confidence: 99%
“…The amino acid residues of VEGF-A important for interacting VEGFR-2 are shaded in red. This figure was adapted from Muller et al (30,31).…”
Section: Construction Of Vegf-e Nz-7mentioning
confidence: 99%
“…The computational study by Young and Roux on the conformational changes undergone by the tyrosine kinase Src during the active/inactive transitions, illustrates how the active and inactive state correspond to two distinct conformation ensembles and how different pathways can be followed for their interconversion [14]. NMR studies [15] and crystal structures containing several copies of the same kinase in the asymmetric units [16] provide valuable insights into the flexibility of the active or inactive conformation of a particular protein kinase (VEGFR -Vascular endothelial growth factor receptor -in both cited examples). In the following section, we will present the mechanisms by which the conformational equilibrium of kinases is regulated.…”
Section: The Inactive Conformationmentioning
confidence: 99%